STUDY OF ANALGESIC EFFICIENCY AND SAFETY OF THE TRANSVERSUS ABDOMINIS PLANE BLOCK IN FEMALE PATIENTS AFTER HYSTERECTOMY - O. V. Smirnova; V. Kh. Timerbaev; P. G. Genov; N. V. Shavrina; O. V. Mayorova; O. Yu. Rebrova (Вестник анестезиологии и реаниматологии)
Hysterectomy is an extensive surgical intervention, which is accompanied by heavy post surgical pain syndrome. Despite mainstreaming of the combined anaesthesis concept, which implies the simultaneous prescription of several analgesics with different mechanisms of action, frequently the quality of postoperative anesthesia continues to be unacceptable. Another option of the problem solution is to introduce the additional regional anesthesia practices, in particular the nerve block anesthesia in the transversus abdominis plane. This study allowed concluding that the block anesthesia of transversus abdominis plane block before hysterectomy does not result in significant reduction of postsurgical pain syndrome and morphine consumption during the first day after surgery, while significantly increases time of the first demand for morphine and helps reducing the dermic hyperalgesia area postoperatively.